Genome-Wide Identification and Cold Stress Response Mechanism of Barley Di19 Gene Family - Wenbo Chai; Chao Yuan; Shufen Li; Hanyuan Xu; Qing Zhu; Hongtao Li; Wei Ji; Jun Wang (Biology)
The Di19 (Drought-induced 19) gene family encodes Cys2/His2-type zinc finger proteins that are known to be involved in plant responses to various abiotic stresses, including drought, salinity, and temperature extremes. However, little is known about their roles in barley (Hordeum vulgare), particularly in cold stress adaptation. This study aimed to conduct a comprehensive genome-wide analysis of the barley genome to identify Di19 gene family members and examine their expression patterns under cold stress, providing theoretical support for stress-resistant barley breeding. By aligning Di19 gene sequences from Arabidopsis and rice and using BLASTp, seven HvDi19 genes were identified in barley. Bioinformatics analysis revealed that all members contain a conserved Cys2/His2-type zinc finger domain and nuclear localization signals. Phylogenetic analysis grouped the HvDi19 genes into four subfamilies, with three homologous gene pairs, and Ka/Ks analysis indicated strong purifying selection. Tissue-specific expression analysis showed significant variation in HvDi19 expression across barley organs. Under cold stress, different barley varieties exhibited distinct HvDi19 gene expression profiles: for instance, HvDi19-1 was downregulated in cold-tolerant varieties, whereas HvDi19-7 showed increased expression in a cold-tolerant mutant, suggesting their potential roles in modulating cold response. These findings reveal the evolutionary conservation and cold-responsive expression characteristics of the HvDi19 gene family, laying a foundation for future functional studies. The results also provide important molecular resources for the genetic improvement of cold tolerance in barley, contributing to the development of stress-resilient crop varieties under climate change.